1962
DOI: 10.1063/1.1732627
|View full text |Cite
|
Sign up to set email alerts
|

Ionic Complexes of Xe and C2H2 Produced by the Radiolysis of These Gases

Abstract: Binaqr mixt?re~ of. acetylene and the noble gases were irradiated by 90 ev electrons at pressures up to 1.3 mm III the IOruzation chamber of a research mass spectrometer. Various proportions of the mixtures and ~ range of pressures were emp~oyed ~n this study. Ionic complexes, [XeC2H]+ and [XeC~2J+, were observed In the C2J:I2-~e system. The intenSIty ratio [XeC~2]+ /[XeC2H]+ increased linearly with increasing pressure. No 10ruC complexes were observed in the other mixtures. A series of reactions involving Xe+… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
10
0

Year Published

1965
1965
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 16 publications
0
10
0
Order By: Relevance
“…Several groups of investigators have reported the formation by ion-molecule reactions in a mass spectrometer of molecular ions containing rare gas atoms (1)(2)(3)(4)(5)(6)(7)(8). Such ions have included ZH+ (1)(2)(3)(4) and small amounts (less than 1 percent of the total ionization) of ZCmHn+ (m = 1, 2; n = 0 to 4) (1-3, 5,6), ZY+ (Y = Cl, Br, I, 0) (5), ZC2N2+ (7), Z2+ (1,2,8,9), ZN2+ (9), and ZCO+ (9), where Z is a rare gas atom, usually xenon.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Several groups of investigators have reported the formation by ion-molecule reactions in a mass spectrometer of molecular ions containing rare gas atoms (1)(2)(3)(4)(5)(6)(7)(8). Such ions have included ZH+ (1)(2)(3)(4) and small amounts (less than 1 percent of the total ionization) of ZCmHn+ (m = 1, 2; n = 0 to 4) (1-3, 5,6), ZY+ (Y = Cl, Br, I, 0) (5), ZC2N2+ (7), Z2+ (1,2,8,9), ZN2+ (9), and ZCO+ (9), where Z is a rare gas atom, usually xenon.…”
mentioning
confidence: 99%
“…Such ions have included ZH+ (1)(2)(3)(4) and small amounts (less than 1 percent of the total ionization) of ZCmHn+ (m = 1, 2; n = 0 to 4) (1-3, 5,6), ZY+ (Y = Cl, Br, I, 0) (5), ZC2N2+ (7), Z2+ (1,2,8,9), ZN2+ (9), and ZCO+ (9), where Z is a rare gas atom, usually xenon. In a different series of studies the production of rare gas-alkyl ions resulting from the /3--decay of the corresponding isoelectronic radioactive alkyl halides has been observed (10)(11)(12).…”
mentioning
confidence: 99%
“…This increase in rate has been explained in terms of an initial charge transfer reaction involving the rare gas ion for those noble gases which have a higher ionization energy than CzNz (2). Xenon has been viewed as an exception because of its relatively low ionization energy and it has been argued that the simple charge transfer theory cannot explain the observations with xenon additive (3). An alternative mechanism has been proposed in which a complex of the type [XeCIN?lf is invoked as an intermediate in a sequence of steps [ I ] to [3] [I] Xe -+ Xe' + e- [2] Xe' + C2N2 + [XCCZNZ*] ' where n and m equal 1 to 4 but 12 is not necessarily equal to tn.…”
Section: Introductionmentioning
confidence: 99%
“…An alternative mechanism has been proposed in which a complex of the type [XeCIN?lf is invoked as an intermediate in a sequence of steps [ I ] to [3] [I] Xe -+ Xe' + e- [2] Xe' + C2N2 + [XCCZNZ*] ' where n and m equal 1 to 4 but 12 is not necessarily equal to tn. p = 4 -tz and q = 4 -m (1,3). Neutral cyanogen can continue to react with the ionic species produced in step [3] to form polymeric ions which ultimately can lead to neutral products by ion-ion or ion-electron recombination.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation